Characteristics of Japanese Garden - Jonuzakov Abduvali Esirgapovich; Djuraeva Gulchehra Nuruldlaevna; Gaibullaeva Muattar Olimjonovna (Researchparks Publishing, 2022)
The article briefly discusses the emergence of garden art in Japan, its main types and analyzes the main features of the Japanese garden.